Estimation of apparent thermal inertia of roofing materials from aerial thermal imagery - Emanuele Mandanici; Gabriele Lo Grasso; Maria A. Tini; Antonio Zanutta (Scientific Reports)
Abstract The rapid expansion of urban areas and soil sealing is enhancing the Urban Heat Island (UHI) phenomenon, especially during heat waves. The different thermal inertia of the building materials compared to natural surfaces is one of the major driving factors of UHI. The present contribution aims to test a methodology for mapping the Apparent Thermal Inertia (ATI)—a proxy that can be derived from remote sensing data—of roofing surfaces at the scale of an entire city and with a high spatial resolution. Day and night aerial thermal images with the resolution of 0.5 m were acquired over two test areas in Bologna (Italy), together with satellite multispectral data. Statistics on the buildings in the test areas are computed considering different classes of roofing materials (e.g. bituminous sheath, clay tiles, metal sheet, gravel tiles). Observed median ATI values for each class range from 0.03 to 0.09 K $$^{-1}$$ - 1 with interquartile ranges between 0.02 and 0.14 K $$^{-1}$$ - 1 , so the intra-class variability in some cases appears higher than the variability among different material classes, proving the importance of ATI mapping for UHI investigations.